Biological activities and characterization of the pod extracts from sompoi (Acacia concinna linn) grown in northern Thailand - Poomanee W. (IJPPS, 2015)
© 2015, International Journal of Pharmacy and Pharmaceutical Sciences. All Rights Reserved. Objective: Sompoi or Shikakai (Acacia concinna Linn.) pod extracts were produced and investigated for antioxidant and antityrosinase activities together with the determination of their total phenolic and flavonoid content. In addition, phytochemical screening, cytotoxic effect and HPLC-fingerprint of the extract were also performed. Methods: The pods of A. concinna were extracted using three different solvents including 95%ethanol, 50%ethanol and deionized water and named as ethanolic extract (ET), freeze-dried hydroethanolic extract (HEF), Spray-dried hydroethanolic extract (HES), freeze-dried aqueous extract (HF), and spray-dried aqueous extract (HS). Antioxidant activity of the extracts were determined by three different assays including 1-Diphenyl-2-picrylhydrazyl (DPPH)-radical scavenging assay, 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS)-radical scavenging assay and linoleic acid peroxidation assay. Total phenolic content in each extract was evaluated using folin-ciocalteu spectrophotometric assay and the total flavonoid content was also determined using aluminium chloride colorimetric assay. Cytotoxic effect on human peripheral blood mononuclear cells (PBMCs) was investigated using MTT assay. HPLC-fingerprint of the selected extract was finally analysed. Results: HES showed the greatest radical scavenging activity on DPPH and ABTS assays with IC50 of 0.8280±0.0131 mg/ml and 0.1418±0.0012 mg/ml, respectively. Moreover, it showed the highest inhibition on lipid peroxidation with IC50 of 1.8751±0.0307 mg/ml. Among five extracts, HES contained the highest amount of gallic acid and rutin expressed as gallic acid equivalent value (GAE) of 100.51±0.06 mg/g and rutin equivalent value (RE) of 14.67±0.01 mg/g. Therefore, its highest antioxidant activity was due to its highest phenolic and flavonoid content. The %viability of HES-treated PBMCs was comparable to ascorbic acid at each individual concentration. The HPLC-fingerprint of HES, detected at the wavelength of 280 nm, showed one major peak at 9.88 min that can be used as a marker of the HES. Conclusions: A. concinna pod extracts showed good in vitro antioxidant and antityrosinase activities with moderate total phenolic and flavonoid content. HES showed the greatest activity with safety profile comparable to ascorbic acid. It might be a promising approach for application in the cosmetic or cosmeceutical products.